The effects of thermal treatment and resin type on physical and mechanical properties of Kenaf stalk particleboard - Ali Pesaraklu (Regional Information Center for Science and Technology (RICeST), 2013)
The objective of this study was to manufacture water resistant kenaf stalk particleboard.Twenty seven boards were produced using 170 °C steam treated kenaf particles, 30 and 60minute treatment time and three resin types include urea-formaldehyde, melamineformaldehydeand a mixture of fifty percent each. Physical and mechanical properties weremeasured and the results analyzed in a complete random design plan and by the factorialanalysis. The results showed that boards made from treated particles with 60 minute treatmenttime and Urea Formaldehyde resin had the highest bending strength. Modulus of elasticity(MOE) improved with an increase in treatment time. The greatest MOE was achieved with theboards produced using urea-formaldehyde and the greatest MOE was achieved with the boardsbonded with urea-melamine-formaldehyde resin. Moreover, with increasing treatment time from30 to 60 minutes internal bond strength (IB) reduced. Thickness swelling and water absorptionof the boards was significantly improved with increasing treatment time.